Review—Development of Advanced Rechargeable Batteries: A Continuous Challenge in the Choice of Suitable Electrolyte Solutions. Issue 14 (9th October 2015) - Erickson, Evan M.; Markevich, Elena; Salitra, Gregory; Sharon, Daniel; Hirshberg, Daniel; de la Llave, Ezequiel; Shterenberg, Ivgeni; Rosenman, Ariel; Frimer, Aryeh; Aurbach, Doron
Abstract : Non-aqueous, rechargeable battery development is one of the most important challenges of modern electrochemistry. Li ion batteries are a commercial reality for portable electronics with intensive efforts underway to apply this technology to electro-mobility. Extensive investigations of high energy density Li-sulfur and Li-oxygen systems have also been carried-out. Efforts to promote high energy density power sources for electric vehicles have been accompanied by intensive work on the development of rechargeable sodium and magnesium batteries for load-leveling applications. The electrolyte solution is a key consideration in all batteries determining cell stability, cycle life, and safety. This review discusses the importance of solution selection for advanced, high-voltage, Li ion batteries, sodium ion batteries, as well as Li-sulfur, Li-oxygen and magnesium batteries. Li ion battery standard solutions are discussed and their further optimization is outlined. Limitations of Li metal electrodes are explained. Unique problems in the use of conventional non-aqueous solutions for Li-oxygen batteries, related to intrinsic stability, are delineated. Finally, electrolyte solutions for Mg batteries are briefly reviewed, concluding that only the relatively inert ethereal solutions are suitable for future consideration. Several systems exhibit wide electrochemical windows and reversible behavior with Mg anodes, however compatibility with high-voltage/high-capacity cathodes remains a major challenge.